2021
DOI: 10.1186/s13059-021-02414-y
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated changes in gene expression kinetics underlie both mouse and human erythroid maturation

Abstract: Background Single-cell technologies are transforming biomedical research, including the recent demonstration that unspliced pre-mRNA present in single-cell RNA-Seq permits prediction of future expression states. Here we apply this RNA velocity concept to an extended timecourse dataset covering mouse gastrulation and early organogenesis. Results Intriguingly, RNA velocity correctly identifies epiblast cells as the starting point, but several traject… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 79 publications
0
44
0
Order By: Relevance
“…By contrast, with dynamo ’s modeling framework, the labeling data (labelled and total RNA) yielded velocity flows that closely recapitulate the established knowledge of hematopoiesis ( Figure 3B right). Previous studies have reported that biased capture of intron regions via mispriming in droplet-based scRNA-seq libraries ( La Manno et al, 2018 ; Qiu et al, 2020a ) and dynamic RNA transcription rates ( Barile et al, 2021 ; Bergen et al, 2021 ) may result in inaccurate RNA velocity flow. Indeed, when inspecting the expression kinetics of lineage marker genes, such as PF4 , a Meg lineage marker ( Paul et al, 2016 ), we found that the spliced and unspliced RNAs were undetectable in progenitors, but its expression switched on rapidly in the Meg lineage ( Figure 3C , left subpanels of Figure 3D , E ) with the unspliced RNA present at a much lower level, consistent with the unsuccessful capture of its introns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, with dynamo ’s modeling framework, the labeling data (labelled and total RNA) yielded velocity flows that closely recapitulate the established knowledge of hematopoiesis ( Figure 3B right). Previous studies have reported that biased capture of intron regions via mispriming in droplet-based scRNA-seq libraries ( La Manno et al, 2018 ; Qiu et al, 2020a ) and dynamic RNA transcription rates ( Barile et al, 2021 ; Bergen et al, 2021 ) may result in inaccurate RNA velocity flow. Indeed, when inspecting the expression kinetics of lineage marker genes, such as PF4 , a Meg lineage marker ( Paul et al, 2016 ), we found that the spliced and unspliced RNAs were undetectable in progenitors, but its expression switched on rapidly in the Meg lineage ( Figure 3C , left subpanels of Figure 3D , E ) with the unspliced RNA present at a much lower level, consistent with the unsuccessful capture of its introns.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the implicit assumption of a constant transcription rate for cscRNA-seq data ( Barile et al, 2021 ; Bergen et al, 2020 ; La Manno et al, 2018 ), dynamo models the transcription rate for labeling data as a variable that depends on measured new RNA and can therefore vary across genes and cells. Collectively, the unbiased measurements of the nascent RNA and the modeling assumption of a transcription rate that differs for each gene in each cell correctly led to positive velocities of PF4 for Meg lineage cells and more broadly corrected the velocity flow ( Figure 3B , E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that, in the presence of cell annotations, BRIE2 can be a useful tool to select relevant genes (differential momentum genes) which provide a smoother and more interpretable description of cell transitions within RNA velocity studies. The importance of selecting trajectory-informed genes for RNA velocity is also evidenced in another recent study [ 23 ].…”
Section: Discussionmentioning
confidence: 90%
“…The TF Gata1 plays an important role in erythropoiesis as it regulates multiple downstream genes in erythroid cell development [ 15 ]. In vitro and in vivo studies of hematopoietic cells that lack the normal expression level of Gata1 , show that the lack of Gata1 halts erythroid differentiation [ 48 , 49 ]. Our model also predicts a block of erythroid differentiation in the absence of Gata1 with a single attractor state resembling the MEPs ( Fig 6F ).…”
Section: Resultsmentioning
confidence: 99%